Sistem Pakar Diagnosa Penyakit Pada Sistem Pencernaan Kelinci Menggunakan Metode Fuzzy Expert System - Tiffani Astrid; Taronisokhi Zebua; Anggiat M Hatuaon Sihite (Journal of Information System Research (JOSH), 2020)
Diseases of the digestive system are a type of disease that often attacks rabbits. This disease is also one of the causes of death in rabbits. This is based on interviews with veterinarians who say that, if diseases of the digestive system are not given the treatment quickly and precisely it will cause death in rabbits. Most veterinarians only open practices in big cities, so it is not uncommon for rabbit breeders who are late in giving treatment to diseases of the digestive system suffered by their pet rabbits. Based on the above problems, it is necessary to create an expert system that can help rabbit keepers and veterinarians in diagnosing diseases in the digestive system of rabbits, because so far there has not been any application to deal with this. The Fuzzy Expert System method will calculate every symptom experienced by rabbits by using the inference method from mamdani. In the Mamdani method, both input and output variables are divided into one or more fuzzy sets. The end result will be done by the process of processing a fuzzy set obtained from the composition of fuzzy rules to produce output in the form of a number in the fuzzy set domain, while this process is called affirmation (defuzzification). From the results of testing the system using the visual basic 2008 program is good to use, but still needs a lot of development in applying it to the expert system